Waqf As a Sustainable Solution: Addressing Climate Change Impacts on Real Estate Through Perpetual Endowment and Community Benefit - Abdul Kader, Sharifah Zubaidah Syed; Baharudin, Mohammad Hidir; binti Mustafa, Maizatun; Mohd Yusoff, Rahmawati; binti Abdul Manaf, Zati Ilham; Djafri, Fares (AIBPM Publisher, 2024)
Climate change poses significant risks to real estate, including extreme weather events, rising sea levels, and shifting climate patterns, threatening property integrity, and market value, and increasing maintenance and insurance costs. Traditional real estate markets often react, resulting in inadequate short-term solutions. In contrast, waqf, which focuses on everlasting endowment and communal benefit, provides a proactive and comprehensive approach to the management of real assets. Sustainability and long-term management in waqf can mitigate property price impacts. This study aims to explore the potential of waqf in addressing climate change impacts on real estate, emphasizing how its principles can be leveraged to enhance resilience and sustainability in the real estate sector. The research adopts a qualitative approach, analyzing primary and secondary materials through governing statutes, reported cases, and data from respective administrative bodies. This study finds waqf properties can be designated for uses promoting environmental sustainability, such as green spaces, conservation areas, and sustainable agriculture. By preserving natural environments, waqf properties can buffer against climate-related disasters, protecting nearby real estate and maintaining property values. In addition, waqf can provide financial assistance for climate adaptation and mitigation initiatives by reinvesting income into projects that improve climate resilience, such as improvements to infrastructure, energy-efficient building retrofits, and the development of early warning platforms. However, integrating waqf in addressing climate change impacts faces challenges, including legal and administrative hurdles, lack of awareness, and the need for capacity building. All in all, by leveraging its principles of sustainability, community benefit, and long-term stewardship, waqf can enhance the resilience of real estate assets and contribute to sustainable urban development